Ratas lactantes e não lactantes diferem quanto à sensibilidade ao HgCl2: efeito protetor do ZnCl2 - Oliveira, Vitor Antunes de (2012)
Mercury is a divalent metal found in the liquid state at room temperature without biological function. Occupational exposure to this metal occurs mainly in industrial activities and agriculture. Its toxicity seems to be due to affinity for sulfhydryl groups and oxidative stress induction. Studies show that mercury causes physiological and biochemical changes in animals and humans. Zinc also is a divalent metal, but in contrast, is an essential element for living beings with important metabolic functions. Studies have indicated beneficial effects of this metal against oxidative damage caused by many toxic substances, including mercury. The objective of this study was to investigate the effect of ZnCl2 and HgCl2 on effect markers and oxidative damage of lactating rats (LR) and non-lactating rats (NLR). Adults LR and NLR received one dose of 27 mg/kg of ZnCl2 (subcutaneously) and after 24 hours received one dose of 5 mg/kg HgCl2 (subcutaneously). The animals were killed 24 hours after the last administration. Kidneys, liver, brain and blood were collected to perform the biochemical test. δ-aminolevulinate dehydratase (δ-ALA-D) activity were analyzed in kidney, liver, brain, and blood; non-protein, total thiols ascorbic acid levels in kidney, liver and brain; catalase activity in kidney and liver; serum urea and creatinine levels; and alanine aminotranferase (ALT) activity in serum and liver. The weights of animals and organs were also analyzed. No alterations were observed in the brains of LR and NLR; ascorbic acid levels also was not changed in tissues analyze. LR and NLR exposed to mercury showed a decrease of kidney total SH levels and an increase of urea and creatinine levels. NLR exposed to mercury showed an inhibition of kidney, liver and blood δ-ALA-D activity, and liver catalase activity. LR exposed to mercury showed an inhibition of blood δ-ALA-D activity and serum ALT activity. LR showed a decrease of liver absolute weight and an increase of kidney relative weight. NLR showed no changes in body and organs weights. Zinc per se increased liver non-protein thiols levels in LR and NLR and decreased liver absolute weight in LR. The pre-treatment with zinc prevented the inhibition of kidney (partially), liver and blood δ-ALA-D and liver catalase activity in NLR. Zinc also prevented the inhibition of blood δ-ALA-D, serum ALT (partially), the decrease in non-protein SH levels (partially) and increase relative weight of kidneys in LR. Thus, we suggest that LR and NLR differ as the toxicity caused by mercury, and the NLR are more sensitive to these toxic effects than the LR. Zinc shows promising effects against the toxic effects on analyzed parameters.